Cryptocurrency: The Future of Green Investment for Generation Z in Islamic Perspective - Sisdianto, Ersi (ITB AAS Indonesia Surakarta, 2023)
Cryptocurrencies, as digital currencies, present challenges regarding legality and exchange rate fluctuations. Therefore, conducting thorough research is necessary to address the issues associated with cryptocurrencies. This research aims to assess Generation Z's preferences for cryptocurrencies as a form of environmentally friendly investment in the future and examine the Islamic perspective on cryptocurrencies. The sample consisted of Generation Z individuals interested in cryptocurrency investments. The population in this study was 100 people, using a sampling technique, namely purposive sampling, so that the sample used as the object of observation was 10 people. This research uses a qualitative approach, namely directly observing research subjects in their natural atmosphere. The research results show that generation z is very interested in investing in cryptocurrency, because the profits obtained are very significant and in Islamic studies investing in cryptocurrency is still permitted because the reason for investing in cryptocurrency is because there are no currency buying and selling transactions. The legal status of cryptocurrencies is still a matter of heated debate due to the lack of clear regulations regarding digital currencies.